A study of effects on economic indicators for different heat source temperature on thermal storage‐based solar organic Rankine cycle system. Issue 1 (21st January 2020) - Baral, Suresh
Abstract: The solar organic Rankine cycle (ORC) system for power generation with thermal storage type may be one of the promising technologies for prolonging power generation. The thermal storage type of solar ORC system is feasible for investment due to higher power production. In addition, the heat source temperature of the ORC system plays an important role in the investment. The main aim of the study is to investigate the solar ORC with thermal storage systems from the thermoeconomic point of view. The paper provides recommendations for a suitable class of investment in which an ORC system can be economically feasible. Besides, the economics and thermoeconomic analysis is carried out in order to find the cost of electricity production from the solar ORC under various solar source temperatures. The cost of electricity generation is found to be in the range of 0.2/kWh to 0.6/kWh for 120°C and 90°C, respectively. For analysis, different financial scenarios are developed based on the total cost of the solar ORC units. The economic parameters, such as payback period, internal rate of return (IRR) and specific investment cost, are calculated. The payback period is found to be less than 6 years for the thermal storage type of solar ORC system with the IRR to be 15%. This shows that the investment is feasible for medium and large scale solar ORC with thermal storage systems. Abstract : The solar organic Rankine cycle system for power generation with thermal storage type can be one of the promising technology for prolong power generation. The thermal storage type of system is feasible for investment due to increase in power production.